2010
DOI: 10.1158/1078-0432.ccr-09-3411
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Nucleolar Expression of Nucleolin Are Associated with Better Prognosis in Patients with Stage II Pancreatic Ductal Adenocarcinoma

Abstract: Purpose: Nucleolin is a major nucleolar protein that has been shown to be overexpressed in rapidly dividing cells and plays an essential role in cell proliferation and survival. However, the expression and significance of nucleolin in pancreatic ductal adenocarcinoma (PDA) have not been studied.Experimental Design: We used a tissue microarray consisting of 1.0-mm cores of tumor and paired nonneoplastic pancreatic tissue from 69 pancreaticoduodenectomy specimens with stage II PDA. Nucleolin expression was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 31 publications
(35 reference statements)
3
37
0
Order By: Relevance
“…It controls the metabolism of DNA and RNA in the nucleolus (44,45), shuttles proteins into the nucleus (46), provides posttranscriptional regulation of strategic mRNAs in the cytoplasm (47,48), and serves as a ligand for proteins, such as midkine and the heparin-binding growth-associated molecule, on the cell surface (49). NCL is also involved in the proliferation of many types of cancer (34,(50)(51)(52) and serves as a prognosis marker and therapeutic target for cancer treatment (53)(54)(55). Furthermore, NCL also participates in the pathogenic mechanism and mediates the replication of several viruses and/or serves as a cell surface receptor for Escherichia coli O157 (56), Helicobacter pylori (57), RSV (28), adeno-associated virus type-2 (AAV-2) (58), coxsackie B virus (59), and HIV (29).…”
Section: Discussionmentioning
confidence: 99%
“…It controls the metabolism of DNA and RNA in the nucleolus (44,45), shuttles proteins into the nucleus (46), provides posttranscriptional regulation of strategic mRNAs in the cytoplasm (47,48), and serves as a ligand for proteins, such as midkine and the heparin-binding growth-associated molecule, on the cell surface (49). NCL is also involved in the proliferation of many types of cancer (34,(50)(51)(52) and serves as a prognosis marker and therapeutic target for cancer treatment (53)(54)(55). Furthermore, NCL also participates in the pathogenic mechanism and mediates the replication of several viruses and/or serves as a cell surface receptor for Escherichia coli O157 (56), Helicobacter pylori (57), RSV (28), adeno-associated virus type-2 (AAV-2) (58), coxsackie B virus (59), and HIV (29).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Qiu et al [12] indicated that the high expression level of nucleolin was an independent prognostic marker for worse survival of patients with gastric cancer; Zhao et al [13] determined that nucleolin expression independently predicted for worse survival of patients with non small cell lung cancer; Grinstein et al [14] identified nucleolin as activator of human papillomavirus type 18 oncogene transcription in cervical cancer; High levels of nucleolin expression have also been shown to correlate with poor survival in patients with cutaneous melanoma and pediatric intracranial ependymoma [15,16]. In contrast, Peng et al [34] reported that high levels of nucleolar expression of nucleolin may be associated with better prognosis in patients with stage II pancreatic ductal adenocarcinoma. Our study revealed that the increased expression of nucleolin was dramatically associated with aggressive clinicopathological features of patients with HCC, such as advance tumor stage, high tumor grade and high serum level of AFP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be up-regulated in highly proliferative cells and regulated many aspects of DNA and RNA metabolism, chromatin structure, rRNA maturation, cytokinesis, nucleogenesis, cell proliferation and growth [32], [33]. Further, the expression of NCL was reported to be increased in pancreatic ductal adenocarcinoma and the overexpression of the protein was found in other human cancers such as gliomas, melanoma, and non-small cell lung cancer [34][37]. Similarly, our semiquantitative RT-PCR and Western blotting results confirmed on a larger series of specimens the increased expression of NCL in the laryngeal carcinoma, indicating the possibility that the overexpression of this protein is more specific to cancer.…”
Section: Discussionmentioning
confidence: 99%